Water Beetles: Species Diversity and Response to Physico-Chemical Parameters in Different Freshwater Habitats in Samtse, Bhutan - Ghalley, Tez Bdr; Dorji, Ugyen; Dorji, Cheten; Nepal, Arjun; Shacha, Namgay (International Journal of Environment, 2021)
Bhutan is located between the two zoogeographic regions which are assumed to be rich in diversity of water beetles. The study aimed to determine the diversity and distribution pattern of water beetles in different freshwater habitats in Namgaychholing under Samtse district, Bhutan. The study also analysed the association of water beetles with the physico-chemical parameters. The data were collected from four different habitats with sample plot of 3 m × 1 m for a standard time of 1 hour in every plot. A total of 30 species belonging to 7 families were recorded of which Dytiscidae (n=626, RA=51) was the most abundant family and Lacconectus basalis (n=416, RA=34.13) was the most abundant species. The overall Shannon diversity index of the study area was H ′=2.48. Amongst the different habitats, marshy area had the highest Shannon diversity index (H ′=2.45) and stream had the lowest (H ′=1.82). A Kruskal Wallis test on diversity among different habitats showed no significant difference (p<.05). Through a cluster analysis, the species composition between the river and waterlogged showed 100% similarity index. Canonical correspondence analysis showed temperature as a main determining factor affecting the distribution of water beetles. With broad families encompassing the water beetles, similar study on water beetles in different regions of the country is recommended with particular emphasis on different families. Moreover, Bhutan falls in junction of Palearctic and Oriental Zoogeographic regions, which are known to be rich in diversity of water beetles. Hence, study in high-altitude lakes, which are assumed to be rich in diversity of water beetles are recommended despite social beliefs to keep lakes isolated and undisturbed.